Muslim Tourists’ Food and Beverage Needs and Preferences During Travel - Zainol, Noor Azimin; Mustafa, Eshaby; Willibrod, Averyl Tony (UUM Press, 2021)
The Muslim travel market is regarded as an encouraging market in the tourism industry at the current state. Muslim tourists prefer to select a tourist destination whereby Islamic elements are available, which permits them to enjoy their travels without neglecting the religious obligations. These elements undoubtedly will provide an enriching experience during their travels. Therefore, this paper aims to examine experiences faced by Muslim tourists in terms of their needs and preferences in the provision of food and beverage services during their travels. In order to fulfil the study’s aim, 14 international Muslim participants who have travelled internationally were interviewed during the data collection process. The findings revealed that Muslim tourists seek for the convenience of finding Halal outlets/Halal food and prefer restaurants or outlets with certified Halal logo. The participants also expressed their concern regarding the different food culture experience. This study has supported previous literatures on enhancing Muslim customers’ experience in terms of food and beverage provision worldwide. Furthermore, the findings help aid in enhancing the experiences of Muslim tourists during travelling hence supporting the growth of Halal tourism. It is seen that tourist destinations and facilities that can provide the needs of faith of the Muslim tourists will exceed in the creation of memorable and meaningful tourist experience.